Efecto de la compacidad y conectividad para determinar qué tamaño de muestra de material casi mono disperso es lo suficientemente relevante para ser significativa en un análisis mecánico (2021)
The present work presents an analytical approach of discrete elements to show that elemental characteristics of the granular environment can be a starting point to determine how large a sample must be to be sufficiently relevant when performing mechanical physical analysis of the interaction behavior between particles. The foregoing will be analyzed through the LMGC 90 numerical tool, which allows physical simulations in discrete cases and will seek to understand how compactness and connectivity in a particulate space can be descriptive enough to understand the basic behavior of the system.